A composite refractory material for RH refining furnace and preparation method thereof
By using MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory materials and using raw materials such as aluminum-chromium alloy powder for high-temperature sintering, the problem of poor anti-permeability and corrosion resistance of existing refractory materials under high-temperature vacuum conditions is solved, and carbon-free , pollution-free high-performance refractory materials meet the smelting needs of high-quality steel.
Patent Information
- Application Number
- CN202310585028.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The existing refractory materials for RH refining furnaces have poor penetration and corrosion resistance under high temperature vacuum conditions, and have carbon pollution problems, making it difficult to meet the smelting needs of high-quality steel.
Using MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material, alumina powder, magnesium oxide powder and corundum particles as raw materials, carbon-free composite refractory material is prepared by high-temperature sintering to achieve MgAl2O4, MgCr2O4 and MgAlON In-situ compound enhancement.
It significantly improves the anti-permeability, corrosion resistance and alkaline slag resistance of refractory materials, extends its service life, and meets the smelting needs of high-quality steels such as ultra-low carbon steel and clean steel.
Smart Images

Figure CN116655360B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of refractory materials, and in particular relates to a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material for RH refining furnace and a preparation method thereof. Background Art
[0002] Off-furnace refining is a key process in steel production, especially in the production of high-quality clean steel. Off-furnace refining can remove impurities and inclusions in molten steel, and adjust the chemical composition of molten steel and make it uniform. RH vacuum refining technology has the advantages of high efficiency, adaptability to batch processing, low equipment investment and easy operation. It is one of the most important methods in off-furnace refining and is widely used in modern steel plants. The refractory materials used for RH refining furnace lining have a harsh service environment and must withstand long-term high temperature (up to 1700℃) vacuum, scouring and erosion of molten steel, cyclic thermal shock, etc. Therefore, it is required to have high refractoriness, high strength, wear resistance, erosion resistance, good thermal shock resistance, and good vacuum stability.
[0003] The service temperature of refractory materials for RH refining furnace lining may be as high as 1700℃. At present, the refractory materials for RH refining furnace lining in my country are mainly magnesia-chrome bricks (≥50%), and some magnesia-carbon bricks (~5%) are used. The lower trough of RH is the high corrosion area of the entire furnace lining, and electric melting and recombination magnesia-chrome bricks are mainly used. However, the pore structure of electric melting and recombination magnesia-chrome bricks is difficult to control, and the resistance to chemical erosion and molten iron penetration is not ideal. Carbon materials have high thermal conductivity and are not easily wetted by molten slag. Magnesium-carbon bricks developed by introducing carbonaceous raw materials into MgO materials have good resistance to slag and molten iron penetration and erosion, as well as good anti-stripping performance, and the service life is increased by about 15% compared with ordinary magnesia-chrome bricks. However, under high temperature vacuum conditions, C in magnesia-carbon bricks will cause MgO to undergo a reduction reaction, forming Mg(g) and CO(g) to escape, resulting in a loose structure. At the same time, carbon will cause pollution to molten steel, so magnesia-carbon bricks are not suitable for the smelting of low-carbon steel and clean steel.
[0004] In the public literature, "Research on the Application Performance of New Al-Al2O3-MgO Refractory Materials for RH Refining Furnaces" (Tong Shanghao, doctoral dissertation of Beijing University of Science and Technology) and CN202111527731.8 "A Preparation Method of Magnesium-Alon Refractory Materials with Multi-morphology Coexistence for RH Refining Furnaces", it is proposed to use metal aluminum powder, alumina powder and magnesia particles as raw materials, keep them at 500-700℃ for 2-10h, and then keep them at a sintering temperature of 1400-1700℃ for 2-6h to obtain MgAlON-bonded corundum composite refractory materials. In order to meet the needs of industrial applications, the high temperature stability and chemical stability of this material need to be further improved, especially in the RH refining service process, the performance of resisting alkaline slag penetration and erosion is still insufficient, resulting in unsatisfactory service life. The development of a high-performance, pollution-free, carbon-free refractory material for RH refining and its preparation method is a problem that the present invention urgently needs to solve. Summary of the invention
[0005] In order to solve the problems in the prior art that the pore structure of magnesia-chrome bricks (MgO-Cr2O3) for RH refining furnaces is difficult to control, resulting in poor anti-permeability and anti-erosion performance, the carbon in magnesia-carbon bricks (MgO-C) is easily soluble in molten steel, causing carbon increase pollution, and the MgAlON-Al2O3 composite material has unsatisfactory anti-alkaline slag erosion performance. The present invention provides a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material and a preparation method to further improve the performance of the refractory material.
[0006] The technical solution adopted by the present invention is as follows.
[0007] A composite refractory material for RH refining furnace comprises the following raw materials in mass fraction: 50-85wt% of corundum, 5-20wt% of chromium-aluminum alloy powder, 10-30wt% of magnesia, and 2-5wt% of a binder.
[0008] Furthermore, the corundum comprises corundum particles with a particle size of 3-1 mm and <1 mm and active alumina fine powder <5 μm; the particle size of the magnesia is <0.5 mm.
[0009] Furthermore, the Cr content in the aluminum-chromium alloy is 2% to 60% by mass.
[0010] Furthermore, the mass percentage of the corundum particles in the corundum is 80% to 95%, and the mass percentage of the aluminum oxide fine powder is 5 to 20%.
[0011] Furthermore, the binder is a thermosetting phenolic resin binder.
[0012] The preparation method of the composite refractory material for the RH refining furnace comprises the following steps:
[0013] (1) mixing corundum, aluminum-chromium alloy powder, magnesia and binder in a certain proportion to make a mud material;
[0014] (2) pressing the clay material into a composite body and drying the body;
[0015] (3) The composite green body is sintered at high temperature to obtain a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material.
[0016] The mass fraction ratio of corundum, titanium aluminum alloy powder, magnesia and binder in step (1) is as follows: 50-85wt% of corundum, 5-20wt% of chromium aluminum alloy powder, 10-30wt% of magnesia, and 2-5wt% of binder.
[0017] Furthermore, the drying in step (2) is to dry the green body at a temperature range of 120 to 200° C. for 10 to 50 hours.
[0018] Furthermore, the high temperature sintering in step (3) is to heat the furnace to 1200° C. to 1700° C. at a rate of 3 to 20° C. / min under air atmosphere conditions and keep the temperature for 1 to 8 hours.
[0019] Furthermore, the kiln includes a tunnel kiln, a shuttle kiln, and an electric kiln.
[0020] The present invention also provides an application of a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material as an inner lining in an RH refining furnace.
[0021] The reaction principle of the present invention is as follows: in an air atmosphere, when the system temperature reaches about 800°C, the AlCr alloy particles in the AlCr-Al2O3-MgO composite body absorb O2 in the atmosphere and begin to be significantly oxidized to generate highly active Al2O3 and Cr2O3, accompanied by a certain volume expansion, filling the pores and refining the pores; as the O2 in the atmosphere is consumed, the oxygen partial pressure inside the body decreases, and the AlCr alloy further reacts with N2 to generate AlN; as the temperature further increases, the newly generated highly active Al2O3, Cr2O3 and AlN further react with MgO in the system to in-situ generate high-performance MgAl2O4, MgCr2O4 and MgAlON reinforcement phases.
[0022] Beneficial effects: The present invention uses aluminum-chromium alloy powder, aluminum oxide powder, magnesium oxide powder and corundum particles as raw materials to prepare a carbon-free AlCr-MgO-Al2O3 composite body, and obtains an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON by high-temperature sintering, that is, a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material. The present invention uses a high-melting-point AlCr alloy as a raw material as a precursor for synthesizing Al2O3, Cr2O3 and AlN intermediate phases, and reduces the potential barrier to be overcome for in-situ synthesis of MgAl2O4, MgCr2O4 and MgAlON multi-compounds through a two-step reaction mechanism of gas-solid reaction and solid-solid reaction, thereby reducing the reaction temperature, while achieving efficient synthesis and uniform distribution thereof, refining pores, and optimizing the composition and microstructure of the material. MgAlON has excellent resistance to molten steel and slag corrosion and thermal shock, MgAl2O4 and MgCr2O4 have excellent resistance to alkaline slag corrosion and oxidation resistance. The synergistic effect of the three can greatly improve the service life of the refractory materials of the lining of the RH refining furnace, while meeting the smelting needs of high-quality steels such as ultra-low carbon steel and clean steel.
[0023] The specific performance is as follows:
[0024] (1) In the RH refining service environment, C in the MgO-C material in the prior art is easily dissolved in molten steel and pollutes the molten steel. The AlCr-MgO-Al2O3 composite refractory material of the present invention is an Al2O3 composite material with TMgAl2O4, MgCr2O4 and MgAlON synergistically in-situ reinforced after high-temperature sintering, which is a new type of carbon-free refractory material with excellent chemical stability and will not pollute the molten steel; at the same time, the in-situ synthesis of the reinforcing phase can fill the pores, refine the pores, and optimize the material structure, thereby further improving the material's anti-penetration and anti-corrosion properties.
[0025] (2) The present invention uses aluminum-chromium alloy as raw material, whose melting point is much higher than that of metal aluminum (such as Figure 1 As shown in the figure, when the temperature reaches 800℃, the solid aluminum-chromium alloy reacts with the atmosphere (gas-solid reaction) with more kinetic advantages and a faster reaction rate, which is conducive to the efficient and large-scale generation and uniform distribution of Al2O3, Cr2O3, and AlN intermediate phases, thereby promoting the controllable synthesis of MgAl2O4, MgCr2O4, and MgAlON at lower temperatures;
[0026] (3) The present invention adds AlCr alloy and sintering in air atmosphere to synthesize MgAl2O4, MgCr2O4 and MgAlON reinforcement phases in situ, wherein MgAlON has excellent resistance to erosion by molten steel; the synthesis of MgAl2O4 spinel is accompanied by a certain volume expansion, which can effectively refine the pores, optimize the structure, and further improve the anti-corrosive medium penetration performance; MgCr2O4 spinel has excellent resistance to alkaline slag, which can greatly improve the alkaline slag corrosion resistance of a single MgAlON-Al2O3 composite material. The synergistic effect of the three can greatly improve the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the Al-Cr binary phase diagram of the present invention. DETAILED DESCRIPTION
[0028] Example 1
[0029] 50wt.% of corundum (wherein the mass percentage of corundum particles is 95% and that of alumina fine powder is 5%), 30wt.% of magnesia, and 20wt.% of aluminum-chromium alloy powder are mixed, and 4wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain an AlCr-MgO-Al2O3 composite material blank, and dried at 120°C for 24 hours. The dried AlCr-MgO-Al2O3 blank is heated to 1400°C at a heating rate of 10°C / min and kept warm for 4h for sintering. In air atmosphere, when the system temperature reaches about 800℃, the AlCr alloy particles in the AlCr-Al2O3-MgO composite body absorb O2 in the atmosphere and begin to oxidize significantly, generating highly active Al2O3 and Cr2O3; as O2 in the atmosphere is consumed, the oxygen partial pressure inside the body decreases, and the AlCr alloy further reacts with N2 to generate AlN; as the temperature further increases, the newly generated highly active Al2O3, Cr2O3 and AlN further react with MgO in the system to generate high-performance MgAl2O4, MgCr2O4 and MgAlON reinforcement phases. Finally, an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON is obtained.
[0030] The obtained Al2O3 composite refractory material in-situ reinforced by MgAl2O4, MgCr2O4 and MgAlON was tested and found to have a phase composition of Al2O3, MgAl2O4, MgCr2O4 and MgAlON, an apparent porosity of 11.2%, and a room temperature compressive strength of 276 MPa.
[0031] Example 2
[0032] 85wt.% of corundum (wherein the mass percentage of corundum particles is 90% and the mass percentage of alumina fine powder is 10%), 5wt.% of aluminum-chromium alloy powder, and 10wt.% of magnesia powder are mixed, and 4wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain an AlCr-MgO-Al2O3 composite material blank, and dried at 200°C for 12 hours. The dried AlCr-MgO-Al2O3 blank is heated to 1600°C at a heating rate of 5°C / min and kept warm for 3h to obtain an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON.
[0033] The obtained Al2O3 composite refractory material with in-situ composite reinforcement of MgAl2O4, MgCr2O4 and MgAlON was tested to have a phase composition of Al2O3, MgAl2O4, MgCr2O4 and MgAlON, an apparent porosity of 12.8%, and a room temperature compressive strength of 206 MPa.
[0034] Example 3
[0035] 65wt.% of corundum (wherein the mass percentage of corundum particles is 95% and the mass percentage of alumina fine powder is 5%), 20wt.% of aluminum-chromium alloy powder, and 15wt.% of magnesia powder are mixed, and 5wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain an AlCr-MgO-Al2O3 composite material blank, and dried at 150°C for 48 hours. The dried AlCr-MgO-Al2O3 blank is heated to 1200°C at a heating rate of 15°C / min and kept warm for 8h to obtain an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON.
[0036] The obtained Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON was tested and found to have a phase composition of Al2O3, MgAl2O4, MgCr2O4 and MgAlON, an apparent porosity of 10.1% and a room temperature compressive strength of 197 MPa.
[0037] Example 4
[0038] 55wt.% of corundum (wherein the mass percentage of corundum particles is 95% and the mass percentage of alumina fine powder is 5%), 15wt.% of aluminum-chromium alloy powder, and 30wt.% of magnesia powder are mixed, and 4.5wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain an AlCr-MgO-Al2O3 composite material blank, and dried at 120°C for 50 hours. The dried AlCr-MgO-Al2O3 blank is heated to 1700°C at a heating rate of 20°C / min and kept warm for 2h to obtain an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON.
[0039] The obtained Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON was tested and found to have a phase composition of Al2O3, MgAl2O4, MgCr2O4 and MgAlON, an apparent porosity of 11.6% and a room temperature compressive strength of 319 MPa.
[0040] Example 5
[0041] 80wt.% of corundum (wherein the mass percentage of corundum particles is 92% and the mass percentage of alumina fine powder is 8%), 10wt.% of aluminum-chromium alloy powder, and 10wt.% of magnesia powder are mixed, and 3.5wt.% of phenolic resin binder is added to the above mixture, mixed evenly, pressed and molded to obtain an AlCr-MgO-Al2O3 composite material blank, and dried at 200°C for 10 hours. The dried AlCr-MgO-Al2O3 blank is heated to 1500°C at a heating rate of 3°C / min and kept warm for 1h to obtain an Al2O3 composite refractory material reinforced by in-situ composite of MgAl2O4, MgCr2O4 and MgAlON.
[0042] The obtained Al2O3 composite refractory material in-situ reinforced by MgAl2O4, MgCr2O4 and MgAlON was tested and found to have a phase composition of Al2O3, MgAl2O4, MgCr2O4 and MgAlON, an apparent porosity of 14.1% and a room temperature compressive strength of 282 MPa.
Claims
1. A composite refractory material for RH refining furnace, characterized in that: The method comprises the following raw material compositions by mass fraction: 50-85 wt% of corundum, 5-20 wt% of aluminum-chromium alloy powder, 10-30 wt% of magnesia, 2-5 wt% of binder, in-situ synthesis of MgAl2O4, MgCr2O4 and MgAlON reinforcement phases, and the chemical formula is MgAl2O4-MgCr2O4-MgAlON-Al2O3.
2. The composite refractory material for RH refining furnace according to claim 1, characterized in that: The corundum includes corundum particles with a particle size of 1-3 mm and <1 mm and active alumina fine powder <5 μm; the particle size of the magnesia is <0.5 mm.
3. The composite refractory material for RH refining furnace according to claim 1, characterized in that: The Cr content in the aluminum-chromium alloy powder is 2% to 60% by mass.
4. The composite refractory material for RH refining furnace according to claim 1 or 2, characterized in that: The mass percentage of the corundum particles in the corundum is 80% to 95%, and the mass percentage of the aluminum oxide fine powder is 5 to 20%.
5. The composite refractory material for RH refining furnace according to claim 1, characterized in that: The binder is a thermosetting phenolic resin binder.
6. The composite refractory material according to any one of claims 1 to 5, characterized in that: Lining for RH refining furnaces.
7. The method for preparing the composite refractory material for RH refining furnace according to any one of claims 1 to 5, characterized in that: The steps include: (1) Corundum, aluminum-chromium alloy powder, magnesia and binder are mixed and stirred in a certain proportion to make a mud material, wherein 50-85 wt% of corundum, 5-20 wt% of chromium-aluminum alloy powder, 10-30 wt% of magnesia and 2-5 wt% of binder are mixed and stirred; (2) pressing the clay material into a composite green body and drying the green body; (3) The composite green body is sintered at high temperature to obtain a MgAl2O4-MgCr2O4-MgAlON-Al2O3 composite refractory material.
8. The preparation method according to claim 7, characterized in that: The drying step (2) is to dry the green body at 120-200 o C temperature range for 10 to 50 hours.
9. The preparation method according to claim 7, characterized in that: The high temperature sintering in step (3) is carried out in a kiln under air atmosphere at 3 to 20 o C / min rate to 1200°C~1700°C and keep warm for 1~8 hours.
10. The preparation method according to claim 9, characterized in that: The kilns include tunnel kilns, shuttle kilns and electric kilns.
Citation Information
Patent Citations
Preparation method of multi-morphology coexisting MgAlON refractory material for RH (Ruhrstahl Heraeus) refining furnace
CN114478030A
Preparation method for magnesium-chromium refractory material
CN108484139A
Microporous MgAlON composite corindon material preparation method
CN1880267A